2019
DOI: 10.1016/j.jped.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-processed food consumption among infants in primary health care in a city of the metropolitan region of São Paulo, Brazil

Abstract: High consumption of ultra-processed foods among children under 1 year of age was found. Both maternal socioeconomic status and time until the child's first appointment at the primary healthcare unit were associated with the prevalence of ultra-processed food intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 19 publications
2
23
0
6
Order By: Relevance
“…In addition, we observed an elevated prevalence of UPF consumption for all The total was lower for some variables due to missing information children. These results are similar to other studies that evaluated early childhood food consumption in Brazil [10,25]. UPF consumption in the first 2 years of life is not recommended because they normally present an elevated energy density and high levels of sugars, fat, sodium and additives, they are hyper palatable, induce the child to frequent consumption and negatively influence future food preferences.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, we observed an elevated prevalence of UPF consumption for all The total was lower for some variables due to missing information children. These results are similar to other studies that evaluated early childhood food consumption in Brazil [10,25]. UPF consumption in the first 2 years of life is not recommended because they normally present an elevated energy density and high levels of sugars, fat, sodium and additives, they are hyper palatable, induce the child to frequent consumption and negatively influence future food preferences.…”
Section: Discussionsupporting
confidence: 89%
“…The breastmilk intake was associated with lower odds of consuming UPF by children. Some studies reported that breastmilk intake is related to lower consumption of UPF and of sweetened beverages among children between 6 and 12 months [10,15,19]. Our results brings unprecedented data about breastmilk as a long-term protection factor for UPF consumption in the first 2 years, not investigated in previous studies.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…2,3 However, other researchers have identified that the nutrient content of highly processed foods varies widely, 4 and that nutrientdense foods can be found at all levels of processing, 5 indicating that food choices within categories may be important. 4 Limited research to date has indicated that even very young children consume some UPF in infancy 6,7 and early childhood, 8 potentially in substantial amounts. For example, data from Brazil, a developing country where dietary guidelines are aligned with avoiding UPF items, 9 indicates that preschoolers obtain as much as 41.8% of their daily energy from UPF.…”
mentioning
confidence: 99%
“…Many of these foods, although fortified with vitamins and minerals, are also rich sources of food additives and considered ultra-processed foods (62,65) . Recent data from studies conducted in Brazilian children have shown that the introduction of ultra-processed foods occurs before the 6th month of life, and about 6 months, the prevalence of ultra-processed foods intake is already 43 % (65–67) . In our study population, most of the mothers offering milk other than breast milk from the first month of life did it as a combined preparation with wheat, oat and rice-based industrialised powder product as previously described (68) .…”
Section: Discussionmentioning
confidence: 99%